2019
DOI: 10.1186/s13568-019-0749-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of ascomycin production via a combination of atmospheric and room temperature plasma mutagenesis in Streptomyces hygroscopicus and medium optimization

Abstract: Ascomycin, a key intermediate for chemical synthesis of immunosuppressive drug pimecrolimus, is produced by Streptomyces hygroscopicus var. ascomyceticus . In order to improve the strain production, the original S. hygroscopicus ATCC 14891 strain was treated here with atmospheric and room temperature plasma to obtain a stable high-producing S. hygroscopicus SFK-36 strain which produced 495.3 mg/L ascomycin, a 32.5% incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Meanwhile, the dynamic profiles of ascomycin biosynthesis after 96 hr differed at various DMSO concentrations (0.2%, and 0.6%; Figure d). In addition, according to the result of Figure d, the time course of ascomycin production clearly revealed that ascomycin yield continuously increased and reached the highest at 168 hr, which is in agreement with a previous report (Yu et al, ). In summary, these results suggest that the regulation of intracellular metabolic events involved in ascomycin biosynthesis could be disturbed by DMSO treatment.…”
Section: Resultssupporting
confidence: 92%
“…Meanwhile, the dynamic profiles of ascomycin biosynthesis after 96 hr differed at various DMSO concentrations (0.2%, and 0.6%; Figure d). In addition, according to the result of Figure d, the time course of ascomycin production clearly revealed that ascomycin yield continuously increased and reached the highest at 168 hr, which is in agreement with a previous report (Yu et al, ). In summary, these results suggest that the regulation of intracellular metabolic events involved in ascomycin biosynthesis could be disturbed by DMSO treatment.…”
Section: Resultssupporting
confidence: 92%
“…It was due to the high effectiveness of an orally used cyclosporin A that is a cyclic peptide accompanying 11 amino acids [ 23 , 24 ], which led to the discovery of this novel class of compounds [ 7 ]. Tacrolimus (FK506), the analog of ascomycin [ 9 , 11 ] was first produced by S. tsukubaensis in 1984 [ 25 ]. After its discovery, another macrolactam was discovered similarly as ascomycin and cyclosporin A in an antifungal screening method of fermentation broths [ 7 , 26 ] named rapamycin (sirolimus) which is also an immunosuppressant, antifungal, antitumor, and anti-aging drug [ 7 , 27 ].…”
Section: Main Textmentioning
confidence: 99%
“…Yu et al studied S. hygroscopicus ATCC 14891 for the production of ascomycin and identified seven co-transcription units in the ascomycin biosynthetic gene cluster, including fkbW , fkbU , fkbR1/R2 , fkbE/F/G , fkbB/C/L/K/J/I/H , fkbO/P/A/D/M , and fkbS/Q/N which were responsible for the synthesis of ascomycin with yield improvement. To determine the expression level, one gene in each of the seven co-transcription units ( fkbW , fkbU , fkbR1 , fkbE, fkbB , fkbO , fkbS ) was selected and results revealed that the expression of four co-transcription units ( fkbW , fkbU , fkbB/C/L/K/J/I/H , and fkbO/P/A/D/M ) were responsible for twofold higher improved yield of ascomycin in S. hygroscopicus SFK-36 in comparison to strain ATCC 14891 [ 11 ]. Another study was conducted by Wang et al where three pathways (aminoacyl-tRNA biosynthesis; phenylalanine, tyrosine, and tryptophan biosynthesis; and pentose phosphate pathways) were studied, from which aromatic amino acid and pentose phosphate biosynthesis pathway were seen to be responsible for the synthesis of precursor molecule involved in ascomycin biosynthesis.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations